Physics from Axioms - Esterhuyse, Willem Francois (JOURNAL OF ADVANCES IN PHYSICS, 2019)
We introduce a definition of Time and Photons from four Axioms. Basically you take a 4-dimensional manifold, transform them into two superimposed Riemann Spheres and isolate a circle (call this Pp) in one of the spheres. Then one specifies the circle to turn by a unit amount (the turn is an quantum rotation: turn from state A to state B without visiting the in between states) as measured along the circle, every time the Pp encounters a space point. Space fluctuates and expands so this does not give a static circle Pp. The circle’s infinity point stays at the north pole of the Riemann Sphere for any finite rotation since: infinity - constant = infinity. Using this one can define basic spacetime and from basic spacetime, Time can be defined if we require special particles to be in the particles of a clock. We go on to define photons and antiphotons. The model predicts that there is a direction in which photons (from the same process) are never emitted. We continue to define a pi-minus.